2018
DOI: 10.3892/etm.2018.6308
|View full text |Cite
|
Sign up to set email alerts
|

Impact of proteasome inhibitor MG‑132 on expression of NF‑κB, IL‑1β and histological remodeling after myocardial infarction

Abstract: The aim of the present study was to investigate the impact of carbobenzoxy-Leu-Leu-leucinal (MG-132) on myocardial remodeling in rats with myocardial infarction (MI) and investigate the possible underlying mechanisms. The rat model of MI was established, followed by administration of MG-132 (MG group), pyrrolidine dithiocarbamic acid (PDTC group) or normal saline (MI group) for 28 days. The expression of nuclear factor-κB (NF-κB) p65, interleukin 1β (IL-1β) and matrix metalloproteinase 2 (MMP-2), as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(27 reference statements)
0
1
1
Order By: Relevance
“…64 Hence, when MMP-2 expression was reduced with IL-1b, an increase in collagen synthesis was found. 63 In the present study, we observed in PPNL-treated groups, regardless of the suture technique, a decrease in MMP-2 expression and an increase in collagen synthesis, mainly type I. We speculate that PPNL action is mediated by immune cells; however, the PPNL anti-inflammatory effect did not alter MMP-9 levels.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…64 Hence, when MMP-2 expression was reduced with IL-1b, an increase in collagen synthesis was found. 63 In the present study, we observed in PPNL-treated groups, regardless of the suture technique, a decrease in MMP-2 expression and an increase in collagen synthesis, mainly type I. We speculate that PPNL action is mediated by immune cells; however, the PPNL anti-inflammatory effect did not alter MMP-9 levels.…”
Section: Discussioncontrasting
confidence: 41%
“…64 Hence, when MMP-2 expression was reduced with IL-1β, an increase in collagen synthesis was found. 63…”
Section: Discussionmentioning
confidence: 99%